The economic crisis vs. the labour market in Poland - Miczyńska-Kowalska, Maria (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Poland, like other EU countries, was affected by the economic crisis of 2008 which began in the United States. The impact of the crisis in the US on the financial systems of other countries was related to toxic assets secured by real estate which started to have no value because of the collapse of the mortgage market. The situation of Poland and other peripheral EU countries in the era of the Great Recession was relatively good. This was because Polish banks did not invest in toxic assets. Thus, the direct financial channel did not affect the Polish economy. By contract, the financial markets affected it indirectly through fluctuations in asset prices, the availability of money and the change in the intensity of capital flows. Accordingly, the Polish situation regarding employment and unemployment had peculiar characteristics that distinguished it from other EU countries
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 475, s. 183-194
Keywords: labour market; economic crisis; unemployment; employment; forms of counteracting unemployment; rynek pracy; kryzys gospodarczy; bezrobocie; zatrudnienie; formy przeciwdziałania bezrobociu